Emerging Concepts in Immune Thrombocytopenia - Swinkels, Maurice; Rijkers, Maaike; Voorberg, Jan; Vidarsson, Gestur; Leebeek, Frank W. G.; Jansen, A. J. Gerard (Frontiers in Immunology, 2018)
Immune thrombocytopenia (ITP) is an autoimmune disease defined by low platelet counts which presents with an increased bleeding risk. Several genetic risk factors (e.g. polymorphisms in immunity-related genes) predispose to ITP. Autoantibodies and cytotoxic CD8+ T cells mediate the anti-platelet response leading to thrombocytopenia. Both effector arms enhance platelet clearance through phagocytosis by splenic macrophages or dendritic cells, and by induction of apoptosis. Meanwhile, platelet production is inhibited by CD8+ T cells targeting megakaryocytes in the bone marrow. CD4+ T helper cells are important for B cell differentiation into autoantibody secreting plasma cells. Regulatory T cells are essential to secure immune tolerance, and reduced levels have been implicated in the development of ITP. Both Fcγ-receptor dependent and -independent pathways are involved in the etiology of ITP. In this review, we present a simplified model for the pathogenesis of ITP, in which exposure of platelet surface antigens and a loss of tolerance are required for development of chronic anti-platelet responses. We also suggest that infections may comprise an important trigger for the development of auto-immunity against platelets in ITP. Post-translational modification of autoantigens has been firmly implicated in the development of autoimmune disorders like rheumatoid arthritis and type 1 diabetes. Based on these findings we propose that post-translational modifications of platelet antigens may also contribute to the pathogenesis of ITP.